PENDEKATAN PEMBELAJARAN BERBASIS INKUIRI DALAM MENINGKATKAN PEMAHAMAN PELAJARAN PKN SISWA KELAS VII SMP NEGERI 2 DAMPAL SELATAN.pdf - -, MULIANA (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Dampal Selatan, 2023)
Motivation to learn will not be built if students still find it difficult to accept PKN lessons, PKN subjects are consideredboring lessons. This phenomenon causes most lessons to be less popular with students because the subject matter isconsidered boring.The aims of this research are 1) to determine the inquiry-based learning process of class VII students at SMP Negeri 2Dampal Selatan, 2) to find out how the use of inquiry-based learning can improve students' understanding of civicslessons for class VII SMP Negeri 2 Dampal Selatan, 3) to find out to what extent implementation of inquiry-basedCivics learning can improve the understanding of class VII students at SMP Negeri 2 Dampal Selatan, 4) to determinestudent responses regarding inquiry-based learning for VII students at SMP Negeri 2 Dampal Selatan.The research results show that 1) The inquiry-based learning approach in improving understanding of Civics lessons forclass VII students of SMP Negeri 2 Dampal Selatan was carried out in 3 (three) cycles with no significant obstacles, 2)The inquiry-based learning approach can improve the understanding of class VII students of SMP Negeri 2 SouthDampal has experienced an increase, 3) An inquiry-based learning approach can increase the creativity of class VIIstudents at SMP Negeri 2 Dampal Selatan, 4) Student responses to the inquiry-based learning approach inunderstanding class VII Civics subject matter at SMP Negeri 2 Dampal Selatan students are positive.